Microbiological composition of river waters in the Ob' basin (West Siberia) and its associations with hydrochemical indices; IOP Conference Series: Earth and Environmental Science; Vol. 27 : Problems of Geology and Subsurface Development - Savichev O. G. Oleg Gennadievich; Tokarenko O. G. Olga Grigorievna; Pasechnik E. Yu. Elena Yurievna; Nalivayko N. G. Nina Grigorievna; Ivanova Е. A.; Nadeina L. V. Louise Vasilievna (Hydrogeochemistry and Hydrogeoecology. Geionformation Systems in Hydrogeochemictry and Hydrogeoecology, 2015)
Title screen